The effects of lactate, acetate, glucose, insulin, starvation and alloxan-diabetes on protein synthesis in perfused rat hearts. - Smith, D M (1986)
Compared with glucose, lactate + acetate stimulated ventricular protein synthesis in anterogradely perfused hearts from fed or 72 h-starved rats. Stimulation was greater on a percentage basis in starved rats. Atrial protein synthesis was not detectably stimulated by lactate + acetate. Insulin stimulated protein synthesis in atria and ventricles. The stimulation of protein synthesis by lactate + acetate and insulin was not additive, the percentage stimulation by insulin being less in the ventricles of lactate + acetate-perfused hearts than in glucose-perfused hearts. Perfusion of hearts from 72 h-starved or alloxan-diabetic rats with glucose + lactate + acetate + insulin did not increase protein-synthesis rates or efficiencies (protein synthesis expressed relative to total RNA) to values for fed rats, implying there is a decrease in translational activity in these hearts. In the perfused heart, inhibition of protein synthesis by starvation and its reversal by re-feeding followed a relatively prolonged time course. Synthesis was still decreasing after 3 days of starvation and did not return to normal until after 2 days of re-feeding.